On Being Religious: Will Religiosity Change Our Perceptions of Pleasure in Reckless Behavior? - Pauline Christianty; Karel Karsten Himawan; Yonathan Aditya (Journal of Educational, Health and Community Psychology, 2019)
Pleasure takes part as an underlying motivation in decision making activities, including when committing conventional and reckless behaviors. Whereas previous studies have confirmed that individuals with higher level of religiosity commit less reckless behaviors, little attention is given to further identify their pleasure perceptions toward performing such actions. This study was intended to fill the gap by demonstrating if higher level of religiosity among emerging adults would change perceptions of pleasure, which in turns reduce the likelihood of performing reckless behavior. A total of 441 data of emerging adults (Mage= 20.69; SD = 1.71) living in Jakarta and Tangerang were gathered. The survey found that there exists a negative influence of religiosity towards perception of pleasure in emerging adults’ reckless behavior. This study suggests that in attempt to reduce reckless behavior, practitioners could use indirect religious approaches, including: adopting religious morality, providing a supportive community, and practicing relaxing rituals.